La langue européenne nommée Tâlyân chez Evliyâ Çelebi et ailleurs - Claudia Römer (Cahiers Balkaniques, 2013)
What does mean the word Tâlyân in Evliyâ? Geographical and historical inaccuracies leave us with a few hesitations, italian, latin, slovenian? And does the word Lâtîn indicate greek, any slavic language, the church slavonic or/and latin? This paper brings us a few lights on these questions.